Risk factor analysis of equine strongyle resistance to anthelmintics. Issue 3 (December 2017) - Sallé, G.; Cortet, J.; Bois, I.; Dubès, C.; Guyot-Sionest, Q.; Larrieu, C.; Landrin, V.; Majorel, G.; Wittreck, S.; Woringer, E.; Couroucé, A.; Guillot, J.; et al.
Abstract: Intestinal strongyles are the most problematic endoparasites of equids as a result of their wide distribution and the spread of resistant isolates throughout the world. While abundant literature can be found on the extent of anthelmintic resistance across continents, empirical knowledge about associated risk factors is missing. This study brought together results from anthelmintic efficacy testing and risk factor analysis to provide evidence-based guidelines in the field. It involved 688 horses from 39 French horse farms and riding schools to both estimate Faecal Egg Count Reduction (FECR) after anthelmintic treatment and to interview farm and riding school managers about their practices. Risk factors associated with reduced anthelmintic efficacy in equine strongyles were estimated across drugs using a marginal modelling approach. Results demonstrated ivermectin efficacy (96.3% ± 14.5% FECR), the inefficacy of fenbendazole (42.8% ± 33.4% FECR) and an intermediate profile for pyrantel (90.3% ± 19.6% FECR). Risk factor analysis provided support to advocate for FEC-based treatment regimens combined with individual anthelmintic dosage and the enforcement of tighter biosecurity around horse introduction. The combination of these measures resulted in a decreased risk of drug resistance (relative risk of 0.57, p = 0.02). Premises falling under this typology also relied more on their veterinarians suggesting practitionners play an important role in the sustainability of anthelmintic usage. Similarly, drug resistance risk was halved in premises with frequent pasture rotation and with stocking rate below five horses/ha (relative risk of 0.53, p < 0.01). This is the first empirical risk factor analysis for anthelmintic resistance in equids. Our findings should guide the implementation of more sustained strongyle management in the field. Highlights: 688 horses have been enrolled for Egg reduction rate measure. Ivermectin remains efficient but fendendazole is not any more. Evidence-based drenching and individual dosing lower resistance risk. Higher biosecurity is associated with higher drug efficacy. Premises with the least pasture constraints show higher drug efficacy.